(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2017)
The performance evaluation process requires a set of criteria and for the purpose of measuring the level of performance achieved by the Unit and the actual level of development of its activities, and in view of the changes and of rapid and continuous variables surrounding the Performance is a reflection of the unit’s ability to achieve its objectives, as these units are designed to achieve the objectives of exploiting a range of economic resources available to it, and the performance evaluation process is a form of censorship, focusing on the analysis of the results obtained from the achievement All its activities with a view to determining the extent to which the Unit has achieved its objectives using the resources available to it and how these resources have been used with a view to identifying and addressing any deviations. contemporary business environment, it is therefore necessary to take into account that financial indicators is no longer sufficient to provide a comprehensive and clear picture of performance, especially as this performance has been accomplished through the implementation of a coherent set of activities that should bring value to the economic unit. This research aims to use the value chain analysis and balanced scorecard to evaluate the performance of economic units.